BENTUK BUDAYA ANAK KELUARGA KAWIN CAMPUR ETNIS TIONGHOA DENGAN ETNIS MELAYU DI KECAMATAN SINTANG - Ratna Bintari; Yohanes Bahari; Imran Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study would to determined the cultural form of mixed marriages between Tionghoa and Malay ethnic families in Sintang Regency. The research  used descriptive method in the form of qualitative research. The data of this study were children from mixed marital families between Tionghoa and Malay ethnic in Sintang Regency. The techniques of data collection in this study were; interviews, observation and documentation, while the tools of data collection were; interview guideline, observation and documentation. The analysis of this study were presented in descriptive qualitative manner using five informants, consisting of some children as a result of mixed marriages between Tionghoa and Malay ethnic in Sintang Regency. The results of this study indicated that there were different forms of religious culture, language and social organization in children in mixed marriages family, where there is a process of cultural domination, cultural aculturation and cultural assimilation in the form of religious culture, language and social organization of mixed marriages between Tionghoa and Malay ethnic groups in Sintang district. Keywords: Cultural Form, Intermarry, Malay Ethnic, Tionghoa Ethnic